2008
DOI: 10.1007/s10108-008-9041-y
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of the effect of labour participation on fertility

Abstract: In this paper we consider the estimation of the causal effect of female labour market status (participation and employment) on fertility. We focus on the sensitivity of the estimated effect to (i) the assumptions about the exogeneity of labour market status; and (ii) the time interval between the measurement of fertility and employment status. Using Spanish quarterly data, we estimate a switching probit model that accounts for the joint determination of both variables. In order to obtain a behavioural effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Gutiérrez-Domenech (2008) finds that the increase in the incidence of unemployment among men tends to delay marriage and then fertility. Alba et al (2009) estimate the causal effect of female labor market status on fertility using Spanish data. They find a positive although non-significant effect of participation and employment on the probability of having the first child, once the endogeneity is accounted…”
Section: Cohort Analysismentioning
confidence: 99%
“…Gutiérrez-Domenech (2008) finds that the increase in the incidence of unemployment among men tends to delay marriage and then fertility. Alba et al (2009) estimate the causal effect of female labor market status on fertility using Spanish data. They find a positive although non-significant effect of participation and employment on the probability of having the first child, once the endogeneity is accounted…”
Section: Cohort Analysismentioning
confidence: 99%
“…Most economic studies of female labour market participation, partnership and fertility have confirmed the importance of human capital, although they vary in the significance they attach to it. Examples for Spain are Bover and Arellano (1995), Ahn andMira (2001), Álvarez-Llorente (2002), Gutiérrez-Domènech (2002, 2005a, 2005b, 2008), De la Rica and Ferrero (2003, Alba and Álvarez-Llorente (2004) and Alba et al (2009). All of them share event history analysis as their methodological approach, while Álvarez-Llorente (2002), Alba and Álvarez-Llorente (2004) and Gutiérrez-Domènech (2005a, 2005b estimate simultaneous events, such as first birth and cohabitation.…”
Section: Female Employment Family Decisions and Trajectories: Review Of The Evidencementioning
confidence: 99%
“…More recently, the life-cycle approach has focused on using the timing and spacing of births over the lifetime span (Hotz and Miller, 1988;Francesconi, 2002;Attanasio et al, 2008). For the specific case of Spain, De la Rica and Ferrero (2003), Gutierrez-Domenech (2008) and Alba et al (2009) amounts were also increased. The first and second child generated a 1200 euros deduction each, while the third and later children generated deductions of 1800 euros.…”
Section: The Spanish Income Tax and Recent Reformsmentioning
confidence: 98%